Cracking the penal code. (Economist, 2012)
The article offers information about the U.S. trial of Sergey Aleynikov, a programmer at the Goldman Sachs financial company. Topics include his conviction for theft of a technology code of the company, the reversal of his conviction by a federal appeals court, and legal protections for financial firms related to technology knowledge.